2016
DOI: 10.1371/journal.pone.0161637
|View full text |Cite
|
Sign up to set email alerts
|

From Sensory Perception to Lexical-Semantic Processing: An ERP Study in Non-Verbal Children with Autism

Abstract: This study examines electrocortical activity associated with visual and auditory sensory perception and lexical-semantic processing in nonverbal (NV) or minimally-verbal (MV) children with Autism Spectrum Disorder (ASD). Currently, there is no agreement on whether these children comprehend incoming linguistic information and whether their perception is comparable to that of typically developing children. Event-related potentials (ERPs) of 10 NV/MV children with ASD and 10 neurotypical children were recorded du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
50
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 79 publications
3
50
2
1
Order By: Relevance
“…First, we tested whether N400 effects could be reliably recorded with a low-cost portable EEG system (Emotiv EPOC+). Second, despite consistent N400 results across studies, populations, and paradigms in groups of participants, few studies have quantified the reliability of the effect at the individual level, and even fewer have done so methodically in individual children (but see Cantiani et al (2016)). We therefore examined the reliability of two auditory paradigms for detecting statistically significant N400 effects in individual children.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, we tested whether N400 effects could be reliably recorded with a low-cost portable EEG system (Emotiv EPOC+). Second, despite consistent N400 results across studies, populations, and paradigms in groups of participants, few studies have quantified the reliability of the effect at the individual level, and even fewer have done so methodically in individual children (but see Cantiani et al (2016)). We therefore examined the reliability of two auditory paradigms for detecting statistically significant N400 effects in individual children.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, to sensitively assess language comprehension in non-speaking children, it is crucial that the paradigm yields reliable responses at an individual level. Despite the large body of literature on the N400 effect in groups of participants, few studies report the reliability of the N400 effect in individual subjects, and even fewer of these studies used child participants (but see Cantiani et al, (2016)). Cruse et al (2014) investigated the sensitivity of the N400 in adults at an individual level using semantic congruency paradigms with spoken sentences and semantically or normatively associated word pairs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different studies, both behavioral and neuroimaging, showed that children with ASD may have difficulties with all language levels. In the large groups of autistic kids, it was demonstrated that children with ASD have impairments in articulation and/or phonological processing (e.g., Cleland et al, 2010;Wolk et al, 2016), problems with lexical-semantic processing (Cantiani et al, 2016), and grammatical impairments (Durrleman et al, 2015;Wittke et al, 2017). However, although children with ASD, according to these studies, have difficulties at all levels of language processing, the simple common profiling of this atypically group is impossible because of the highly heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…As such, it seems to be a wellsuited candidate for the assessment of lexico-semantic processing. The N400 has been widely reported in groups of typical adults, children, and special populations, including recently in autistic children (Cantiani et al, 2016;Coderre et al, 2019;DiStefano et al, 2019). However, despite the recent interest in using N400 as an assessment tool, individual subject level analyses are rarely reported.…”
Section: Introductionmentioning
confidence: 99%